Dynamic Interleukin-6 Level Changes as a Prognostic Indicator in Patients With COVID-19 - Liu, Zeming; Li, Jinpeng; Chen, Danyang; Gao, Rongfen; Zeng, Wen; Chen, Sichao; Huang, Yihui; Huang, Jianglong; Long, Wei; Li, Man; Guo, Liang; Wang, Xinghuan; et al. (Frontiers in Pharmacology, 2020)
Background: Interleukin-6 (IL-6), a proinflammatory cytokine, has been reported to be associated with disease severity and mortality in patients with coronavirus disease 2019 (COVID-19). Yet, dynamic changes in IL-6 levels and their prognostic value as an indicator of lung injury in COVID-19 patients have not been fully elucidated. Objective: To validate whether IL-6 levels are associated with disease severity and mortality and to investigate whether dynamic changes in IL-6 levels might be a predictive factor for lung injury in COVID-19 patients. Methods: This retrospective, single-center study included 728 adult COVID-19 patients and used data extracted from electronic medical records for analyses. Results: We included 120 and 608 patients in the elevated and normal IL-6 groups, respectively. The mortality rate was higher in the elevated IL-6 group than in the normal IL-6 group. Cox proportional hazards and logistic regression analyses for survival (adjusted hazard ratio, 10.39; 95% confidence interval [CI], 1.09–99.23; p=0.042) and disease severity (adjusted odds ratio, 3.56; 95% CI, 2.06–6.19; p<0.001) revealed similar trends. Curve-fitting analyses indicated that patient computed tomography (CT) scores peaked on days 22 and 24. An initial decline in IL-6 levels at 16 days was followed by resurgence to a peak, nearly in tandem with the CT scores. Conclusion: A high IL-6 level is an independent risk factor for disease severity and in-hospital mortality and dynamic IL-6 level changes is a potential predictor for lung injury in Chinese COVID-19 patients. And the findings may guide the treatment of COVID-19 patients.